Determinan Perilaku Menabung Pada Siswa Sekolah Menengah Atas; Peran Literasi Keuangan Sebagai Variabel Intervening - Frisca, Dhea; Widyastuti, Umi; Buchdadi, Agung Dharmawan (Program Studi Administrasi Niaga STIA Said Perintah, 2023)
The low saving rate of students aged 15-17 years is the reason for the purpose of this research, namely to analyze and find out about the influence of financial literacy, financial socialization, peer influence and self-control on saving behavior of high school students in DKI Jakarta and to analyze the influence between financial socialization on saving behavior through financial literacy of high school students in DKI Jakarta as an intervening variable. This research uses quantitative methods. The data collection technique in this study was distributing questionnaires consisting of several statements. The population in this study were high school students in DKI Jakarta with a sample of 287 students in DKI Jakarta who were taken by convenience sampling technique. The data analysis technique used is using several tests including validity tests, reliability tests, model feasibility tests and hypothesis testing through the SPSS 25 and AMOS 24 applications. The conclusion from the results of this study is that financial literacy, financial socialization, peer influence and self-control have an influence positive and significant impact on the saving behavior of high school students as well as financial literacy can be an intervening role that partially plays a role between financial socialization and saving behavior.